MOF-derived porous hollow Ni/C composites with optimized impedance matching as lightweight microwave absorption materials - Wu, Nannan; Zhao, Beibei; Liu, Jiyun; Li, Yaling; Chen, Yunbo; Chen, Lin; Wang, Meng; Guo, Zhanhu (Advanced composites and hybrid materials, 2021)
Electromagnetic wave (EM) pollution caused by rapid development of electric devices has been threatening people’s lives. Thus, the need for high-performance and lightweight microwave absorption materials is becoming more and more urgent. In this concern, this paper reported the successful fabrication of Ni/C composites by adopting the MOF-derived method. The as-prepared Ni/C composites delivered porous and hollow structures with diameters of 1.0–2.0 μm. Their microwave absorption performances were investigated in calcination temperature ranges of 600–800 °C. When tested for microwave absorption, the porous hollow Ni/C microspheres displayed outstanding microwave absorption performances. With a filling ratio of 30 wt%, the porous hollow Ni/C microspheres obtained at 600 °C exhibited minimal reflection loss (RL) of − 32.3 dB at thickness of 1.5 mm. The effective bandwidth with RL below − 10 dB achieved 4.4 GHz with 1.61-mm thickness. For porous hollow Ni/C microspheres obtained at 700 °C, the optimal RL reached − 55.4 dB at 1.53 mm. The results could push the development of MOF-derived magnetic carbon materials as lightweight microwave absorbers with strong absorption. Graphical abstract